Analisis Rantai Pasok dan Efisiensi Pemasaran Ternak Domba Penggemukan di Peternakan Raja Domba Indonesia - Winarto, Ahmad Aji; Amam, Amam; Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu (Universitas Galuh, 2024)
The supply chain system and marketing efficiency need to be considered in a farm to produce high-quality products, ensure efficient distribution of sheep, and realize a sustainable farming business. The aim of this study is to examine the supply chain in terms of product flow, financial flow, and information flow, and to analyze the marketing efficiency of fattening sheep at Raja Domba Indonesia farm. The research location was intentionally chosen to be at Raja Domba Indonesia in Jember Regency. The research method utilized was descriptive and analytical. The data used included both primary and secondary data sourced from Raja Domba Indonesia farm. The technique for determining informants in this study used purposive sampling. Informants consisted of six people, namely the farm owner, administration, financial division, livestock procurement division, sales division, and buyers. The research findings indicate that there are three networks in the supply chain, and the links involved in the supply chain include breeding farmers, livestock groups, Raja Domba Indonesia farm, community farmers, end consumers, catering services, and butchers. The marketing efficiency values for network 1 are 9.5%, for network 2 are 7.8%, and for network 3 are 7.7%. The supply chain for fattening sheep at Raja Domba Indonesia consists of three flows: product flow, financial flow, and information flow, all of which are well integrated. The Conclussion show that the marketing efficiency at Raja Domba Indonesia farm falls into the efficient category because it is below 33%.